2022
DOI: 10.21203/rs.3.rs-1411902/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Biochar and Green Manure on Soil Nutrients and Rhizosphere Soil Fungal Community Structure

Abstract: In order to explore the impact of biochar and green manure on the micro-ecological environment of citrus soil, a field experiment was used to set CK (conventional fertilization), T1 (5.0 kg/biochar) and T2 (5.0 kg/biochar + 10% nitrogen fertilizer reduction + green manure), for measuring the 3 kinds of fertilization affectness to the fungal diversity and community structure of citrus rhizosphere soil. The results showed that, compared with CK, the pH, alkali-hydrolyzable nitrogen, available phosphorus and avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…The observed inverse relationship between pH levels and total nitrogen (TN) content, as well as microbial communities, aligns with previous investigations [66,67]. Consequently, the makeup of soil microbial communities is impacted [68], thereby highlighting the significance of organic matter as a key determinant of fungal communities [69]. The findings of AN and AP in a study conducted by Sun et al [70] exhibited a resemblance to the results observed in the present investigation.…”
Section: Environmental Drivers Of Soil Fungal Communitiessupporting
confidence: 90%
“…The observed inverse relationship between pH levels and total nitrogen (TN) content, as well as microbial communities, aligns with previous investigations [66,67]. Consequently, the makeup of soil microbial communities is impacted [68], thereby highlighting the significance of organic matter as a key determinant of fungal communities [69]. The findings of AN and AP in a study conducted by Sun et al [70] exhibited a resemblance to the results observed in the present investigation.…”
Section: Environmental Drivers Of Soil Fungal Communitiessupporting
confidence: 90%